Process-Oriented Translator Training and the Challenge for E-Learning - Massey, Gary (Meta, 2005)
AbstractRecent cognitive models present translation competence as an open-ended process encompassing a number of mutually dependent, interacting sub-components, which seems to have resulted in a shift towards process-orientation in translator training and created a favourable climate for introducing social constructivist methods to translator education. This paper considers the emergence of a new translator training paradigm and the challenge it poses for e-learning, which by virtue of the key role played by ICT tools in the translation process is well positioned to become an established, integral part of process-oriented, constructivist translator education.